2012
DOI: 10.1128/jvi.00069-11
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Untranslated Regions of Human Enterovirus 71 Impairs Growth in a Cell-Specific Manner

Abstract: Human enterovirus 71 (HEV71) is the causative agent of hand, foot, and mouth disease and associated acute neurological disease. At present, little is known about the genetic determinants of HEV71 neurovirulence. Studies of related enteroviruses have indicated that the untranslated regions (UTRs), which control virus-directed translation and replication, also exert significant influence on neurovirulence. We used an infectious cDNA clone of a subgenogroup B3 strain to construct and characterize chimeras with 5=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Furthermore, after amplification of infectious clones harboring EV71 subgenogroup B3 in SH-SY5Y and RD cell lines, VP1 94 was recently identified and is postulated to be important for cell-type adaptation [36]. Taken together, the region surrounding the VP1 L97R mutation identified in this study likely plays an important role in cell-type adaptation and potentially neurotropism, independent of the EV71 genogroup.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, after amplification of infectious clones harboring EV71 subgenogroup B3 in SH-SY5Y and RD cell lines, VP1 94 was recently identified and is postulated to be important for cell-type adaptation [36]. Taken together, the region surrounding the VP1 L97R mutation identified in this study likely plays an important role in cell-type adaptation and potentially neurotropism, independent of the EV71 genogroup.…”
Section: Discussionmentioning
confidence: 56%
“…The nascent positive-strand RNA is encapsidated. Viral particles are released from infected cells (10).…”
mentioning
confidence: 99%
“…Replacement of the PV internal ribosome entry site (IRES), with that of a non-neurotropic human rhinovirus (HRV), was found to stably attenuate PV in animal models [149,150] . In HEV71, it was shown that deletion of stem-loop domain Z within the 3'-untranslated region attenuates the growth of a HEV71-HRV2-IRES chimera in neuroblastoma cells [151] . Another strategy employed to generate stably attenuated vaccine strains is to increase the replication fidelity of the 3D polymerase.…”
Section: Live-attenuated Vaccinementioning
confidence: 99%